Seorang Wanita dengan Straight Back Syndrome - Ika Christine (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2018)
Skeletal deformity may alter thoracic configuration, which leads to misdiagnosis of the cardiovascular system. An absence of normal thoracic kyphosis has been identified to be a cause of “pseudo-heart disease”. This deformity is characterized by a reduced antero-posterior diameter of chest that causing a compression of the heart and great vessel. It is well known as the Straight Back Syndrome. Although this abnormality is subtle, it may generate leftward displacement of the heart, resulting cardiac murmurs, chest pain, and tracheal compression. Straight back syndrome may closely mimicking several cardiac diseases, such as mitral valve prolapse, ventricle septal defect, and pericardial absence. Chest x-ray has been known to be the most convenient diagnostic tool for this syndrome. Careful clinical assessment of this syndrome may avoid patients from unnecessary medication. This literature presents a case of a 36 year-old woman who was misdiagnosed with ventricular septal defect from the physical examination, transthoracic echocardiography, and transesophageal echocardiography. However, the right and left diagnostic catheterization resulted normal findings. Consequently, the patient was suggested to discontinue completely her medication